Yfirfærsla á málaflokki fatlaðs fólks frá ríki til sveitarfélaga - Gylfi Jónsson 1983- (2012)
The aim of this study was to look into how the transfer of the affairs of disabled people from the state to the municipalities had proceeded. The process of the transfer was looked into and then one municipality, Reykjavik, was chosen. There I took a closer look on the policy and implementation concerning service for disabled people. I did a qualitative research in the autumn of 2012. Eight interviews were taken with professionals who had been involved directly in the transfer or worked on the affairs of disabled people before or after the transfer. There are six municipal services in Reykjavík. I interviewed one person from each centre where I tried to get an interview with the one who had the best insight into the affair. Furthermore I interviewed an employee at The Association of Local Authorities in Iceland and one at The Ministry of Welfare. The main conclusions are that my interviewees believed that having decided on and gone through with the transfer was the right thing to do. They believed that services closer to the people would be a better choice. And now the person that uses the services only has to go to one place to receive it. A conciderable amount of money is needed for the affair. My interviewees had the opinion that interdisciplinary work was proceeding well. Key words: Management changes, disabled people, Goverance Markmið rannsóknarinnar var að athuga hvernig yfirfærsla á málaflokki fatlaðs fólks frá ríki til sveitarfélaga hefði gengið fyrir sig. Heildarferli yfirfærslunnar var skoðað og síðan var eitt sveitarfélag, Reykjavíkurborg, valið og skoðað nánar með tilliti til stefnu og framkvæmdar á þjónustunni við fatlað fólk. Um var að ræða eigindlega rannsókn sem fór fram haustið 2012. Tekin voru átta viðtöl við fagaðila sem höfðu komið beint að vinnu við yfirfærsluna eða unnið við málaflokkinn fyrir og eftir yfirfærslu. Þjónustumiðstöðvar Reykjavíkurborgar eru sex talsins og var eitt viðtal tekið á hverri þjónustumiðstöð og leitast var við að fá viðmælanda sem var hvað mest inn í málaflokknum. ...